Character Education Strengthening Strategy Based On School Culture For Senior High School Students - Jamaludin, Sophan; Wasliman, Iim; Rostini, Deti; Helmawati, Helmawati (International Journal of Educational Research & Social Sciences, 2022)
The era of globalization characterized by free competition and excellence, and supported by modern information technology, turned out to provide problems for the world of education in the development of the character of the nation. Among the problems is the optimal involvement of envirormental input consisting of families, communities and stakeholders, to the process of implementing strengthening character education strategies based on humanist education principles. Based on some of these problems, the study focused on: "Character Education Strengthening Strategy based on school culture for high school students." In general, this study aims to describe: Environmentalobservation, formulation of school culture-based strengthening character education strategy for high school students, implementation of strengthening character education strategy, evaluation of strengthening character educationstrategy, obstacles to implementation of strengthening character education strategy, solutions from obstacles to the implementation of strengthening character education strategies, and impact of implementation of strengthening character education strategies. The study uses a qualitative approach with descriptive analysis, sourced from principals, deputy principals, teachers, and students. The data collection tools used are observations, interviews, and documentation studies. The results of this study generally show that these two Institutions have established the formulation, implementation, and evaluation of strategies of the school's culture-based strengthening character education for high school students well in accordance with the principles of strategic management. Specifically: 1) Environmental analysis conducted by the Principal at the two Educational Institutions runs in accordance with strategic management theory and can be used as a first step before formulating and choosing a school culture-based strengthening character education strategy for high school students. 2) The formulation of strengthening character education strategy implemented at these two Educational Institutions is in accordance with the principles of strategic management and government policy. 3) Implementation and implementation of school culture-based strengthening character education Strategy for students at two institutions can be implemented properly in accordance with the principles of strategic management, although in his research researchers found some obstacles, but all of them can be sought solutions. 4) Evaluation related to the School's culture-based strengthening character education strategy for students has been arranged and running well. This can be seen with the articles and rules that have been set by the school related to what students do, their development and activities while in school and outside school. 5) In general, obstacles in implementing the strengthening of school culture-based character education in the two institutions include the limitations of integrated policy tools in realizing character values; shifting ethical values in the life of the nation and state; affected by information technology. 6) Everyone involved in the Education process must know very well the function of national education and teachers must have a commitment in participating in realizing every function of national education. 7) The formation of students of strong character and religious character, an effective, conducive and efficient learning environment, an integrated curriculum between co-curricular, intra-curricular and extra-curricular, and the creation of a good school culture.